1991
DOI: 10.2337/diab.40.7.873
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Free Radical Effects in Sciatic Nerve in Experimental Diabetes

Abstract: We previously reported the presence of endoneurial hypoxia, ischemia, impairment of the blood-nerve barrier, and reduction of norepinephrine and 6-ketoprostaglandin F1 alpha in chronic streptozocin-induced diabetic neuropathy (SDN) and interpreted these findings as suggesting the involvement of oxygen free radicals (OFRs) but did not directly measure indices of OFR activity. In this study, we report on sciatic nerve conjugated dienes, hydroperoxides, norepinephrine, and malondialdehyde in SDN at 1, 4, and 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…AG restored SEP latencies markedly at the 1st week and both compounds significantly improved SEP latencies at the 4th week of the treatment period. Although TBARS may give conflicting results (Low and Nickander 1991), it increases in the early period of STZ-induced diabetes (Low and Nickander 1991), and it has been reported to decrease by antioxidant agents such as butylated hydroxytoluene (Saulis-Liparota et al 1995). The SEP latency measured in our study reflects mainly the cortical conduction time, which consisted a main central and a very short peripheral component.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…AG restored SEP latencies markedly at the 1st week and both compounds significantly improved SEP latencies at the 4th week of the treatment period. Although TBARS may give conflicting results (Low and Nickander 1991), it increases in the early period of STZ-induced diabetes (Low and Nickander 1991), and it has been reported to decrease by antioxidant agents such as butylated hydroxytoluene (Saulis-Liparota et al 1995). The SEP latency measured in our study reflects mainly the cortical conduction time, which consisted a main central and a very short peripheral component.…”
Section: Discussionmentioning
confidence: 56%
“…Raised levels of lipid peroxidation products as a result of oxidative stress have been reported both in human (Nishigaki et al 1981) and STZ -diabetic rats (Low and Nickander 1991;Pitchard et al 1986). Although the exact mechanisms of alloxan and STZ-induced diabetes are not well defined, and in fact may be different, the present study indicates that neuropathic changes emerging after induction with alloxan may share common characteristics with STZ -induced diabetes such as raised levels of lipid peroxidation products (Low and Nickander 1991). Although the exact mechanisms of alloxan and STZ-induced diabetes are not well defined, and in fact may be different, the present study indicates that neuropathic changes emerging after induction with alloxan may share common characteristics with STZ -induced diabetes such as raised levels of lipid peroxidation products (Low and Nickander 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) depletion of myoinositol; (3) reduced activity of Na/K ATPase; (4) increased sorbitol levels; (5) reduced nerve growth factors; (6) increased free oxygen radicals (Low and Nickander, 1991); (7) abnormal mitochondrial function; (8) increased levels of glycated proteins (Jakus and Rietbrock, 2004;Hwang et al, 2005); (9) reduced production of various vasodilatory effectors leading to microangiopathy, tissue ischemia, and hypoxia; (10) activation of nuclear factor k B and protein kinase C that produces inflammatory damage (Vlassara, 1992;Brownlee, 2001); and (11) interaction between the multipotent immunemodulator CD40 ligand and its receptor contributing to further inflammatory insult to the nervous system (El-Asrar et al, 2012). Additional proposed mechanisms relate to direct insulin signaling on neurons and axons; C-peptide deficiency (a by-product of the insulin prohormone originally thought to be inactive); abnormal signaling by advanced glycation end products on neuronal and glial receptors; and activation of poly-ADP-ribose polymerase in microvessels and neurons (Zochodne, 2008;Verrotti et al, 2009).…”
Section: Pathogenesis Of Diabetic Neuropathymentioning
confidence: 99%
“…5 Taurine also has antioxidant properties, 4,9-11 which may explain its role as a scavenger of free radical production in diabetic tissue. 12 Previous studies have shown that taurine prevents glucose-induced lipid peroxidation and excess collagen production in mesangial cells. 13 Moreover, it has been observed that apoptosis is activated in rat 14 and murine tubular cells exposed to high glucose concentrations 2 and that taurine attenuates apoptosis induced by high glucose in human endothelial cells.…”
Section: Introductionmentioning
confidence: 99%